Pardos’ Triumph - Miguel Valerio (Journal of Festive Studies)
On September 13, 1745, the pardo (mixed-race Afro-Brazilian) brotherhood (lay Catholic association) of Nossa Senhora do Livramento (Our Lady of Emancipation) of Recife, Pernambuco, in collaboration with the pardo brotherhood of Nossa Senhora de Guadalupe (Our Lady of Guadalupe) in neighboring Olinda, enthralled Pernambuco’s largest city with a great festival in honor of Blessed Gonçalo Garcia (1556–97). Like many colonial festivals, the festivities included fireworks, artillery salvos, five triumphal carts, seventeen allegorical floats, five different dance performances, and jousting. Yet never before had such an extravagant display of material wealth been made by an Afro-Brazilian brotherhood. The pardo irmãos (brotherhood members) had two important issues they wanted to settle once and for all with this festival. One was the question of Blessed Gonçalo’s pardoness, since the would-be-saint was the son of a Portuguese man and an East Indian woman, and pardoness in Brazil had been defined as the result of white–black miscegenation. The other issue was the popular notion that mixed-race Afro-Brazilians constituted colonial Brazil’s most deviant and unruly socioracial group. In this article, I analyze how mixed-race Afro-Brazilians used the material culture of early modern festivals to publicly articulate claims about their sacro-social prestige and socio-symbolic status. I contend that material culture played a central role in the pardo irmãos’ articulation of their devotion to Blessed Gonçalo and claims of sacro-social and socio-symbolic belonging, and that they used this material culture to challenge colonial notions about their ethnic group.